Implementasi Simple Multi Attribute Rating Technique Untuk Menentukan Lokasi Usaha Waralaba - Ilman Kadori; Abdul Rasyid; Faisal Akbar (INFOKOM, 2023)
Groceries shops, rice stalls, cake shops, shoe shops and mini markets are various types of businesses built by entrepreneurs. Franchise minimarkets are a case study taken in this research because business competition is becoming increasingly fierce and competitive. The lack of experience and knowledge of entrepreneurs, the number of competitors, business support, crowd centers, population density, parking lots, community income and road access and the difficulty of determining the right business location are the causes of the business not developing. One of the successes of a franchise business is influenced by the accuracy in choosing a business location. A strategic business location will determine the number of consumers and profits that have the potential to increase. The method used in this decision support system is the Simple Multi Attribute Rating Technique (SMART), which is a multi-attribute decision-making method. SMART is a comprehensive decision-making model taking into account qualitative and quantitative matters. In this SMART decision-making model, it basically tries to cover every shortcoming of the previous non-computerized models.